Aerobic oxidative dehydrogenation of N-heterocycles over OMS-2-based nanocomposite catalysts: preparation, characterization and kinetic study. Issue 2 (17th December 2019) - Bi, Xiuru; Tang, Tao; Meng, Xu; Gou, Mingxia; Liu, Xiang; Zhao, Peiqing
Abstract : OMS-2-based nanocomposites doped with sodium phosphotungstate were prepared and their remarkably enhanced catalytic activity and recyclability in aerobic oxidative dehydrogenation of N-heterocycles were examined in detail. Abstract : OMS-2-based nanocomposites doped with tungsten were prepared for the first time and their remarkably enhanced catalytic activity and recyclability in aerobic oxidative dehydrogenation of N-heterocycles were examined in detail. Many tetrahydroquinoline derivatives and a broad range of other N-heterocycles could be tolerated by the catalytic system using a biomass-derived solvent as a reaction medium. Newly generated mixed crystal phases, noticeably enhanced surface areas and labile lattice oxygen of the OMS-2-based nanocomposite catalysts might contribute to their excellent catalytic performance. Moreover, a kinetic study was extensively performed which concluded that the dehydrogenation of 1, 2, 3, 4-tetrahydroquinoline is a first-order reaction, and the apparent activation energy is 29.66 kJ mol −1 .